(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper, we discuss the peristaltic and pulsatile flow of a couple stress fluid through porous medium in a channel bounded by flexible walls. The non-linear equations governing the flow through porous medium are solved under perturbation scheme. The flow separation, the formation of bolus and phenomenon of reflux and the velocity filed and the wall stress are investigated analytically and their behavior is discussed computationally.